Long‐term outcomes of standardized colonic stenting using WallFlex as a bridge to surgery: Multicenter prospective cohort study. Issue 4 (1st October 2021) - Kuwai, Toshio; Tamaru, Yuzuru; Kusunoki, Ryusaku; Yoshida, Shuntaro; Matsuzawa, Takeaki; Isayama, Hiroyuki; Maetani, Iruru; Shimada, Mamoru; Yamada, Tomonori; Saito, Shuji; Tomita, Masafumi; Koizumi, Koichi; et al.
Abstract : Objectives: The oncological outcomes, especially high recurrence rate, of bridge‐to‐surgery (BTS) self‐expandable metallic stent (SEMS) placement remain concerning, emphasizing the necessity of standardized SEMS placement. However, its impact on long‐term BTS outcomes is unknown. We investigated the long‐term outcomes of BTS colonic stenting using standardized SEMS placement. Methods: This prospective, multicenter cohort study conducted at 46 hospitals in Japan (March 2012 to October 2013) included consecutive patients with stage II and III obstructive colorectal cancer managed with BTS SEMS placement. The SEMS placement technique was standardized by information dissemination among the participating hospitals. The primary outcome was overall survival (OS) after SEMS placement, and the secondary outcomes were relapse‐free survival (RFS), recurrence, and short‐term outcomes of SEMS placement and surgery. Results: The 1‐, 3‐, and 5‐year OS rates were 94.1%, 77.4%, and 67.4% (Kaplan–Meier), respectively, with high technical success (99.0%, 206/208) and low perforation (1.9%, 4/208) rates. The 1‐, 3‐, and 5‐year RFS rates were 81.6%, 65.6%, and 57.9% (Kaplan–Meier), respectively, and the overall recurrence rate was 31.0% (62/200). The RFS rate was significantly poorer in patients with perforation ( n = 4) than in those without perforation ( n = 196) (log‐rank P = 0.017); moreover, perforation was identified as an independent factor affecting RFS (hazard ratio 3.31; 95% confidence interval 1.03–10.71, multivariate Cox regression). Conclusion: This large, prospective, multicenter study revealed satisfactory long‐term outcomes of BTS colonic stenting using a standardized SEMS insertion method, which might be specifically due to the reduced perforation rate. (UMIN000007953).